Legalitas Layanan Tambahan (Ancillary Sevices) Dalam Gats Annex on Air Transport Services Dan Peraturan Nasional Indonesia - Ratna Ayu Widiaswari (Jurnal Interpretasi Hukum, 2025)
The liberalization of air transport in public and international passenger transport has an important role in the process of international integration and the development of other sectors of the economy. Currently, trade on air transport services have been regulated in GATS (General Agreement on Trade In Services) Annex on Air Transport Services. One form of airline service liberalization is additional services or ancillary services on air transport. Within GATS itself there are several ancillary services that are not strictly regulated. Indonesia as one of the countries ratifying the provisions of GATS shall implement the provisions on additional services and ancillary services on air transport in Indonesian laws and regulations. This research applied normative legal research as a method that refers to legal norms to understand the application of legal norms to the presented facts. The purpose of this research is to analyze the legality of the ancillary services on air transport in GATS annex on air transport services and indonesian regulations. From the results of the research can be concluded that there is still the type of air transport ancillary services that has not been regulated in the law of Indonesia. The title of this research Legality of Ancillary Services In GATS Annex On Air Transport Services And Indonesian National Regulations.